Exploring lifestyle and dietary pattern shifts among Saudi adults during COVID-19 pandemic: insights from a cross-sectional examination - Najlaa M. Al-Mana; Tahani A. Zareef; Fatmah A. Albathi; Hala A. Awney; Farah Baeshen; Renad Abdullah (Frontiers in Nutrition)
BackgroundSince the emergence of COVID-19 and the subsequent imposition of lockdown and movement restrictions, the world has witnessed fundamental lifestyle changes including alterations in dietary patterns and food consumption habits. Here, we investigated how the COVID-19 lockdown impacted dietary patterns and eating behaviors in the Saudi population.MethodologyThis cross-sectional study enrolled 427 participants aged 18 years or more, with 258 of them completing the survey. The survey included questions about demographic and dietary patterns during the COVID-19 lockdown. Data were collected and dietary behaviors before and during the lockdown in Jeddah, Saudi Arabia, were analyzed.ResultsThe number of participants who considered lunch as their primary meal significantly decreased (p < 0.001) during the COVID-19 lockdown (74%), compared to before it (86%). By contrast, the number of participants who considered dinner as their primary meal remained almost unchanged (p = 0.079) during (79.1%) and before (84.1%) the lockdown. However, snack consumption significantly increased (p < 0.001) while fast-food consumption significantly decreased (p < 0.01) during the lockdown period. Our results also revealed a significant increase (p < 0.01) in water and coffee intake during the lockdown, with a significant rise in dessert consumption (p < 0.01).ConclusionOur results demonstrate that the COVID-19 lockdown caused a marked shift in dietary patterns and eating behaviors among the Saudi population. Notable changes were observed in overall food preferences after the lockdowns were imposed, with reduced consumption of fast foods and increased fluid intake.